Hydrogel Electrolytes for Quasi-Solid Zinc-Based Batteries - Lu, Kang; Jiang, Tongtong; Hu, Haibo; Wu, Mingzai (Frontiers in Chemistry, 2020)
On account of the high energy density depending on the utilized zinc metal anode of high theoretical capacity and excellent security due to aqueous electrolyte that usually be locked in polymer host referred as hydrogel, quasi-solid zinc-based batteries, have subjected to more and more concerns of researchers. The good water retention and electrolyte load capacity of the hydrogel, contributing to the acquirement of high ionic conductivity and durability of the as-obtained quasi-solid electrolyte, play significant effect on the performance of the devices. Moreover, chemistries of hydrogels can be tuned to endow quasi-solid electrolytes additional function in terms of application scenarios of solid-state batteries. Herein, the frontier disciplines of hydrogel electrolytes for Zn-based batteries were reviewed. The cross-linking process of the polymer networks for hydrogel materials with different functions, such as stretchability and compressibility, self-healing, were also discussed to analysis properties of polymer electrolyte. Based on the merits of functionalized hydrogel, the further application of hydrogel electrolyte in Zn-based batteries is the focus of this paper. The electrochemical performance and mechanical property of Zn-based batteries with functionalized hydrogel electrolyte under extreme conditions were presented to evaluate the crucial role of the polymer hydrogel electrolyte. Finally, the challenges of hydrogel electrolytes for currently developed Zn-based batteries are highlighted with the hope to boost their commercial application in energy conversion devices.